PENGARUH PEMBERIAN INSTENTIF, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT. BANK RAKYAT INDONESIA (BRI) CABANG PANDANARAN SEMARANG) - Destiana, Sisca; Waluyo, Handoyo Djoko; Budiatmo, Agung (Jurnal Ilmu Administrasi Bisnis, 2015)
Human resource had by company have to be powered and paid attention so that they earn to work better for the shake of continuity of company life. See importantly of human resource nya in continuity of life an company, hence company have to design and manage its human resource correctly utilize. Or failure efficacy an company supported by at its employees performance. Good performance, hence existing human resource in company have to have the quality of good also. Some factor able to influence employees performance isÂ  giving of incentive, motivation work and organizational culture. With the background, hence target of which is applied from this research is to know influence giving of incentive, motivation work and organizational culture to employees performance at Bank Rakyat Indonesia (BRI) Pandanaran Branch Semarang.This research which become sampel is Bank Rakyat Indonesia employees (BRI) Pandanaran Branch Semarang amounting to 55 employees from population equal to 120 employees with calculations Slovin. Used by Data type is primary data and sekunder while the analysis of data using frequency tables, cross tables, corelation product moment, simple regression, multiple regression using at SPSS 1.6.Result of research of giving of incentive by parsial have an effect on positive and signifikan to officer performance. Motivation work by parsial positive bepengaruh and signifikan to officer performance. Cultural of organization by parsial there are positive influence and signifikan to officer performance. Giving] of Incentive, motivation work and organizational culture have an effect on by simultan to officer performance. Equal to 69,5% officer performance can influence by giving] of incentive, organizational culture and motivation. While the rest 30,5% explained by other causes outside variableÂ  giving of incentive, motivation work and organizational culture